The Unofficial Anthem of the Tatar People "Tugan Tel" as Political Discourse - Khurmatullina, Rezeda Kamilevna (Journal of History Culture and Art Research, 2018)
The study of the anthem in forging national identity is a contemporary view, which allows us to consider the anthem as a historical source, which reflects both the historical memory and the national identity of the people. The song "Tugan tel", which was first performed in 1909, is passed on by Tatars from generation to generation as a folk tradition, as the symbol of national unity, thanks to which is perceived by the people as an anthem. This song brings together Tatars scattered around the world, helping each of them to feel a sense of ownership of the national origins, language and culture. In Soviet times, when national schools were closed, at various events of the Tatar public "Tugan tel" sang chorus as a protest against the national policy of the center. This song, which talks about the huge role and importance of the Tatar language in the preservation of national culture, has become particularly relevant and acute in connection with the socio-political events that took place in the second half of 2017 in the Republic of Tatarstan on the teaching of the Tatar language in schools. Since art is inextricably connected with a context of historical, social, political, and moral conditions, approaching these issues will be the subject of our discourse. We are also trying to answer the question of how historical memory, national identity, politics and music are related.